READING IS THE FOUNDATION FOR DEVELOPING AN INTELLECTUALLY AND MORALLY REFINED - Meyliyeva Muqaddas Muzaffar qizi; Dusyorova Klara Narmuminovna (Bright Mind Publishing, 2025)
A book is a source of enlightenment that illuminates hearts and leads a person to true perfection. A book not only provides spiritual nourishment to a person, but also teaches healthy thinking and serves as a solid foundation for the future. That is why a book is compared to a person's best friend. Good reading is equivalent to the purification of the soul. A book is an example of a candle that illuminates the darkness of the night, it is sometimes an adviser, sometimes a reprimand, and sometimes a map that shows the way. In Uzbek families, where the Uzbek people have long been considered bookworms, attention to books, careful preservation of books, and reading are among the ancient traditions. Reading among our people was formed in a family environment. It is our priority to convey these ancient values to the future generation.
Keywords: People, personality, upbringing, school, worldview, society, story, poet, poetry, experience, idea, writer.